Blood leakage detection during dialysis therapy based on fog computing with array photocell sensors and heteroassociative memory model. Issue 1 (26th January 2018) - Wu, Jian‐Xing; Huang, Ping‐Tzan; Lin, Chia‐Hung; Li, Chien‐Ming
Abstract : Blood leakage and blood loss are serious life‐threatening complications occurring during dialysis therapy. These events have been of concerns to both healthcare givers and patients. More than 40% of adult blood volume can be lost in just a few minutes, resulting in morbidities and mortality. The authors intend to propose the design of a warning tool for the detection of blood leakage/blood loss during dialysis therapy based on fog computing with an array of photocell sensors and heteroassociative memory (HAM) model. Photocell sensors are arranged in an array on a flexible substrate to detect blood leakage via the resistance changes with illumination in the visible spectrum of 500–700 nm. The HAM model is implemented to design a virtual alarm unit using electricity changes in an embedded system. The proposed warning tool can indicate the risk level in both end‐sensing units and remote monitor devices via a wireless network and fog/cloud computing. The animal experimental results (pig blood) will demonstrate the feasibility.